Menthol as an alternative anaesthetic and sedative for rainbow trout, Oncorhynchus mykiss. Issue 1 (2nd May 2019) - Teta, C; Kaiser, H
Abstract : Menthol is known for its analgesic properties, but relatively little information is available on its potential as an anaesthetic on fish. The purpose of this study was to assess anaesthetic and sedative effectiveness of menthol and its safety in rainbow trout ( Oncorhynchus mykiss ). Juvenile rainbow trout 180 ± 28 g (mean ± SD) within a range of 152–208 g fish −1 were individually exposed to menthol concentrations between 10 and 150 mg l −1 and observed for behavioural responses, induction time to anaesthesia and recovery time. Menthol concentrations of 40–150 mg l −1 induced anaesthesia with varying exposure times. There was an exponential relationship ( p < 0.001) between induction time and menthol concentration. Menthol concentrations of 80–150 mg l −1 induced anaesthesia within three minutes of exposure and fish recovered within three minutes. Induction and recovery data showed that 80 mg l −1 was most suitable for anaesthesia in juveniles of this species. Concentrations of 10–20 mg l −1 had sedative effects. Menthol stock solutions prepared using ethanol and acetone and storage time of stock solutions at room temperature for up to 48 h showed no significant differences in anaesthetic efficiency. When exposure time to menthol was kept constant at three minutes, 22% of fish had temporary cessation of gill ventilation. These fish had longer recovery times than those that did not show that response. Menthol was an effective anaesthetic and could be tested as a sedative for trout.